2005
DOI: 10.4319/lo.2005.50.6.1887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron on algal community composition and physiological status in the Peru upwelling system

Abstract: Phytoplankton community structure in the eastern Equatorial Pacific (EEP) and the Peru upwelling system was determined using ChemTax analysis of pigment data. Photosynthetic efficiencies (F v : F m ), concentrations of macronutrients, iron (Fe), and the redox proteins flavodoxin (Flv) and ferredoxin (Fd) were used to assess the physiological status of the algal communities with respect to Fe. Diel periodicity in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In contrast, the southern coastal upwelling and offshore regions of the Peru Current lack this external supply of iron and the waters evolve into Fe‐limited HNLC “blue waters” containing relatively low diatom biomass and Chl a [ Minas and Minas , 1992; Bruland et al , 2005]. “Blue water” phytoplankton communities are dominated by haptophytes [ Hutchins et al , 2002], whereas large diatoms are the most abundant phytoplankton group inhabiting the coastal upwelling “brown waters” [ Rojas de Mendiola , 1981; Wilkerson et al , 2000; Iriarte and Gonzalez , 2004; DiTullio et al , 2005].…”
Section: Study Regionmentioning
confidence: 99%
“…In contrast, the southern coastal upwelling and offshore regions of the Peru Current lack this external supply of iron and the waters evolve into Fe‐limited HNLC “blue waters” containing relatively low diatom biomass and Chl a [ Minas and Minas , 1992; Bruland et al , 2005]. “Blue water” phytoplankton communities are dominated by haptophytes [ Hutchins et al , 2002], whereas large diatoms are the most abundant phytoplankton group inhabiting the coastal upwelling “brown waters” [ Rojas de Mendiola , 1981; Wilkerson et al , 2000; Iriarte and Gonzalez , 2004; DiTullio et al , 2005].…”
Section: Study Regionmentioning
confidence: 99%
“…The potential for Fe‐limited growth conditions in this region has been demonstrated by Fe enrichment experiments and via comparison of dissolved Fe concentrations, chlorophyll a biomass, phytoplankton fluorescence characteristics, and molecular Fe stress signatures (Bruland et al, ; DiTullio et al, ; Eldridge et al, ; Hutchins et al, ; Martin et al, ). The possible role of cobalt (Co) in (co‐)limiting part of the extant phytoplankton community has also been predicted for this region (Hawco et al, ; Saito et al, ); furthermore, this has been demonstrated directly in the Costa Rica Dome further to the north (Saito et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of phytoplankton groups to total Chl a was calculated using the CHEMTAX matrix factorization software (Mackey et al, 1996). We used an initial ratio matrix that was based on ratios developed by DiTullio et al (2005) and Mackey et al (1996) for the equatorial Pacific and Peruvian upwelling region. Slight modifications were made in order to account for the presence of the pigment aphanizophyll (Apha).…”
Section: Methodsmentioning
confidence: 99%